Strategic Planning of Information Systems for Mosque in Indonesia - Galih Abdul Fatah Maulani; Teten Mohamad Sapril Mubarok (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
Anticipating the era of Society 5.0, communities and organizations are required to have integrated and comprehensive information access, including the management of mosques in Indonesia. This study aims at providing a strategic planning in the form of a portfolio for future application of mosques management information system services. This study was conducted with reference to Ward and Peppard’s strategic plan for information systems, which included SWOT analysis, critical success factor method and McFarlan’s strategic grid. The results showed the mosque management must have several applications, mapped into 4 quadrants (strategic, high potential, key operation, and support). It is expected that this application portfolio can help managers of mosques in Indonesia provide faster, more accurate, and more accountable information.